Marine Prosperity Areas: a framework for aligning ecological restoration and human well-being using area-based protections - Aburto-Oropeza, Octavio; Platzgummer, Valentina; Ferrer, Erica M.; López-Sagástegui, Catalina; Mirabent, Rocío de Guadalupe Abud; Ávalos Galindo, América; Favoretto, Fabio; Giron-Nava, Alfredo; Mendoza Camacho, Isabel; Núñez Sañudo, Claudia; Plascencia de La Cruz, Marisol; Robles, Alejandro (Frontiers in Marine Science, 2025)
Mechanisms for marine ecological protection and recovery, including area-based conservation tools like ‘Marine Protected Areas’ (MPAs) are necessary tools to reach the Aichi Target or the forthcoming 30x30 target set by the Kunming-Montreal Biodiversity Framework. However, full ecosystem recovery takes years to manifest and the idea that MPA protection alone will foster human well-being is frequently contradicted by socio-economic evidence. Therefore, a new framework for marine area-based conservation and ecosystem restoration that reconciles the discrepancies between ecological recovery and socio-economic growth timelines is needed to effectively meet global biodiversity conservation targets. We introduce the concept of ‘Marine Prosperity Areas,’ (MPpA) an area-based conservation tool that prioritizes human prosperity as opposed to passively relying on ecosystem recovery to catalyze social change and economic growth. This concept leverages a suite of tried-and-true community-based intervention and investment strategies to strengthen and expand access to environmental science, social goods and services, and the financial perks of the blue economy. This data-driven framework may be of interest to stakeholders who support traditional area-based conservation models, but also to those who have been historically opposed to MPAs or have been excluded from past conservation processes.